Impact of eptinezumab on work productivity beyond reductions in monthly migraine days: post hoc analysis of the DELIVER trial - Piero Barbanti; Susanne F. Awad; Heather Rae-Espinoza; Stephane A. Regnier; Xin Ying Lee; Peter J. Goadsby (Journal of Patient-Reported Outcomes)
Abstract Background Eptinezumab’s impact on self-reported work productivity in adults with migraine and 2‒4 prior preventive migraine treatment failures is not fully understood. Methodology Electronic diaries captured monthly migraine days (MMDs) reported by patients enrolled in the randomized, double-blind, placebo-controlled DELIVER trial (NCT04418765). The migraine-specific Work Productivity and Activity Impairment questionnaire, administered at baseline and each monthly visit, was a secondary outcome of DELIVER and used to model changes from baseline in self-reported monthly hours of absenteeism (decreased work attendance) and presenteeism (reduced work efficiency while at work with a migraine) in Canada, as the base case. Path analysis illustrated eptinezumab’s impact on work productivity beyond MMDs. Results As MMDs increased, monthly hours of absenteeism increased linearly while those of presenteeism increased quadratically. Best-fit models were improved after including an eptinezumab treatment effect, showing benefit over placebo after controlling for MMD frequency. Compared to placebo, patients treated with eptinezumab (pooled) had a modeled reduction from baseline of 7.2 h/month (absenteeism) (95% CI: −9.9, −4.5; P < 0.001) and 21.4 h/month (presenteeism) (95% CI: −26.3, −16.5; P < 0.001) over weeks 1‒24. Beyond MMD reductions, improvements in patient-identified most bothersome symptom (PI-MBS) and reductions in percent of severe migraine attacks contributed to eptinezumab’s effect. Conclusions Eptinezumab decreased absenteeism and presenteeism based on patient reports, with data highlighting the importance of considering the PI-MBS. The greater change from baseline than placebo in self-reported absenteeism and presenteeism was only partly explained by changes in MMDs, presenting a potential opportunity to decrease the cost of migraine in the workplace. Trial registration ClinicalTrials.gov (Identifier: NCT04418765); EudraCT (Identifier: 2019-004497-25)